2021
DOI: 10.3389/fgene.2021.636236
|View full text |Cite
|
Sign up to set email alerts
|

Haplotypic Associations and Differentiation of MHC Class II Polymorphic Alu Insertions at Five Loci With HLA-DRB1 Alleles in 12 Minority Ethnic Populations in China

Abstract: The analysis of polymorphic variations in the human major histocompatibility complex (MHC) class II genomic region on the short-arm of chromosome 6 is a scientific enquiry to better understand the diversity in population structure and the effects of evolutionary processes such as recombination, mutation, genetic drift, demographic history, and natural selection. In order to investigate associations between the polymorphisms of HLA-DRB1 gene and recent Alu insertions (POALINs) in the HLA class II region, we gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…2 The absence and presence of a variety of structurally dimorphic retroelements within the MHC, such as Alu, SVA, long terminal repeats (LTR), and human endogenous viruses (HERVs), have been used as haplotypic markers and for phylogenetic analyses of population ancestral relationships and diversity. [20][21][22][23][24] The investigation of MHC multilocus haplotypes and disease associations is complicated by the regulatory network of cis-acting multilocus expression units known as haplotypespecific expression quantitative trait loci (eQTL). 2,25,26 These eQTL are controlled by an array of retroelements and DNA transposons, 27 both as binding sites for transcription factors 28 and as sources of regulatory noncoding RNAs.…”
Section: Impact Statementmentioning
confidence: 99%
“…2 The absence and presence of a variety of structurally dimorphic retroelements within the MHC, such as Alu, SVA, long terminal repeats (LTR), and human endogenous viruses (HERVs), have been used as haplotypic markers and for phylogenetic analyses of population ancestral relationships and diversity. [20][21][22][23][24] The investigation of MHC multilocus haplotypes and disease associations is complicated by the regulatory network of cis-acting multilocus expression units known as haplotypespecific expression quantitative trait loci (eQTL). 2,25,26 These eQTL are controlled by an array of retroelements and DNA transposons, 27 both as binding sites for transcription factors 28 and as sources of regulatory noncoding RNAs.…”
Section: Impact Statementmentioning
confidence: 99%
“…For example, ten young AluY indels that are either present or absent in particular human MHC class I and class II haplotypes are useful evolutionary genetic markers of past recombination events, as well as excellent markers for elucidating population phylogenetics and genetic interrelationships [70][71][72] . In this regard, Cun et al recently showed that five different MHC class II dimorphic Alu elements either alone or linked together as haplotypes with HLA-DRB1 alleles can differentiate 12 Chinese minority ethnic groups according to their geographic locations, and correlate them with their population characteristics of language family, migration and sociality 73 .…”
Section: Block Length Bpmentioning
confidence: 99%
“…For comparative and phylogenetic analyses, we used haplotype frequencies data from previously published works (Cun et al., 2021; Kulski et al., 2010; Shi et al., 2014). Genetic distances (Nei, 1972) were computed by the phylip 3.5 package using haplotypic frequencies as raw data (Felsenstein, 1993).…”
Section: Allele Aludpb2 Aludqa2 Aludqa1 Aludrb1 Aluorf10mentioning
confidence: 99%
“…Among the polymorphisms existing in the MHC class II region, there are several polymorphic Alu insertions (POALINs) including five human‐specific ones (AluDPB2, AluDQA2, AluDQA1, AluDRB1 and AluORF10) that are informative lineage markers (Kulski et al., 2010; Kulski et al., 2021). Investigations of the MHC II POALINs in Japanese, Caucasians and Chinese have shown that whether investigated alone or together with the HLA class II alleles, they are informative genetic markers for the identification of allele and haplotype lineages as well as variations within the same and/or different populations (Cun et al., 2021; Kulski et al., 2010). Despite their informativeness, studies on MHC II POALINs are scarce and to our knowledge never reported among African populations.…”
Section: Allele Aludpb2 Aludqa2 Aludqa1 Aludrb1 Aluorf10mentioning
confidence: 99%